کسٹم ڈیوٹی سے متعلق اسلامی نقطۂ نظر: حضرت عمر کے افکار کی روشنی میں ایک مطالعہ: Islamic Approach towards custom duty: A Study in the light of Hazrat Umar’s Thought (Al-Qamar, 2019)
The tax fixed by the government on import and export of goods is called customs. During the time of Hazrat Umar (R.A), the governments of Iran and Rome had a constitution that whenever Muslims entered the borders of traders for trade, they used to collect fixed taxes from them. But when non-Muslim traders entered the Islamic State, no tax was collected from them, which would have caused trade deficit for the citizens of the Islamic State and non-Muslims would have been protected from this deficit. In this regard Hazrat Umar (may Allah have mercy on him) sent an order to the Governors saying: "Receive from them as much as they receive from Muslim traders. Take half a decade from the dhimmi and receive a dirham from the Muslims every forty dirhams, and there is nothing less than 200 dirhams. When the two hundred dirhams arrive, there are five dirhams in them, and when there are more than 200, receive it accordingly. Hazrat Umar suggested to continue trading between non-Muslims and Muslims and also to impose Ashure (tax) on them. However, it was given that the trader from who tax (Ashure) should be collected once a year should not be taken again from any number of times in the year after that. What is the difference between the Ashure of the time of Hazrat Umar (R.A) and today's tax is called customs duty.
Keywords: Custom; duty; Umar; analysis